Effect of 1-naphthalene acetic acid and 6-benzyladenine on micropropagation of strawberry cultivar ‘Praratchatan No.80’ - Sirijan, Mongkon; Pipattanawong, Narongchai; Chaiprasart, Peerasak (Agriculture and Natural Resources, 2019)
The growth was studied of callus, shoots and roots of the strawberry cultivar ‘Praratchatan No.80’ in a sterilized culture on Murashige and Skoog (MS) medium supplemented with different concentrations and combinations of 1-naphthalene acetic acid (NAA) and 6-benzyladenine (BA). Treatments were established as MS medium supplemented with combinations of NAA (0.0 mg/L, 1.0 mg/L, 2.0 mg/L) and BA (0.0 mg/L, 1.0 mg/L, 1.5 mg/L, 2.0 mg/L) with a control (MS medium without supplementation) in a completely randomized design experiment. The results showed that MS medium supplemented with 1.0 mg/L NAA + 1.5 mg/L BA was the best medium to induce callus tissue with a maximum length and width of 2.74 cm and 2.10 cm, respectively. The callus grown on MS medium supplemented with 2.0 mg/L BA generated explants with the highest number of shoots (38.9 shoots/explant). The greatest average length of strawberry shoot was 7.24 cm. The explants from MS supplemented with 2.0 mg/L BA grown on MS without NAA generated the highest numbers of roots (16.9 roots/shoot) and root length (4.31 cm). This formula is a suitable medium for micropropagation of the strawberry cultivar ‘Praratchatan No.80’.